2014
DOI: 10.1007/s13277-014-2185-5
|View full text |Cite
|
Sign up to set email alerts
|

H19 promotes pancreatic cancer metastasis by derepressing let-7’s suppression on its target HMGA2-mediated EMT

Abstract: The long noncoding RNA (lncRNA) H19 has been recently characterized as an oncogenic lncRNA in some tumors. However, the role of H19 in pancreatic ductal adenocarcinoma (PDAC) remains unclear. In this study, we found that not only the levels of H19 was overexpressed in PDAC compared with adjacent normal tissues, but also H19 expression was upregulated remarkably in primary tumors which subsequently metastasized, compared to those did not metastasis. Subsequently, the efficacy of knockdown of H19 by H19-small in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
162
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(177 citation statements)
references
References 42 publications
14
162
1
Order By: Relevance
“…H19 was characterized as an oncogenic lncRNA in some tumors and upregulated remarkably in primary PDAC tumors that subsequently metastasized, compared to those with non-metastasis. H19 also promoted PDAC cell invasion and migration at least partially by increasing HMGA2-mediated epithelial-mesenchymal transition (EMT) through antagonizing let-7 (53). The previous studies also reported several other lncRNAs related to PDAC, such as HULC, PVTI, MAP3K14, PPP3Cb, DAPKI and LOC285194 (54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 90%
“…H19 was characterized as an oncogenic lncRNA in some tumors and upregulated remarkably in primary PDAC tumors that subsequently metastasized, compared to those with non-metastasis. H19 also promoted PDAC cell invasion and migration at least partially by increasing HMGA2-mediated epithelial-mesenchymal transition (EMT) through antagonizing let-7 (53). The previous studies also reported several other lncRNAs related to PDAC, such as HULC, PVTI, MAP3K14, PPP3Cb, DAPKI and LOC285194 (54)(55)(56)(57).…”
Section: Discussionmentioning
confidence: 90%
“…Previous researches highlighted the post-transcriptional repression of HMGA2 by several miRNAs, such as let-7 29 , miR-33a 30 and miR-204 31 . Gong et al found that lncRNA H19 promoted HMGA2-mediated epithelial-mesenchymal transition through antagonizing let-7 32 . Study of Deng et al also showed that a lncRNA, CCAT1 functions as a molecular sponge for let-7 and leads to the derepression of its endogenous targets HMGA2 33 .…”
Section: Discussionmentioning
confidence: 99%
“…H19 promotes EMT via antagonizing let-7 and contributing to HMGA2-mediated EMT in pancreatic ductal adenocarcinoma (17), or by being associated with enhancer of zeste homolog 2 (EZH2) and activating wingless/β-catenin to decrease E-cadherin in bladder cancer (34). H19 has been identified to encode microRNA-675 (miR-675), and a positive feedback loop between H19/miR-675 and Slug has been reported to attenuate E-cadherin and lead to EMT in certain cancer cell lines (16).…”
Section: Discussionmentioning
confidence: 99%
“…H19 is initially suggested as a suppressor for tumor development and metastasis (12,13). However, previously H19 has been proposed as an oncogenic lncRNA in numerous cancers (14,15), and is found to positively regulate the metastatic potential of cancer cells (16,17). In endometrioid endometrial cancer tissues (18)(19)(20), overexpression of H19 exists and is associated with neoplastic cell invasion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation